Development of aerosolized niosome formulation containing gemcitabine and cisplatin for in-vitro cytotoxicity against MRC5 and A549 cell lines - Mohamad Saimi, Norfatin Izzatie (2020)
Gemcitabine (Gem) and cisplatin (Cis) are currently being used for lung cancer treatment has been proven to improve the life expectancy of cancer patients, but they are highly toxic in high dosages. Aerosolized niosome formulation containing a low-dosage Gem and Cis (NGC), as an alternative formulation for lung cancer chemotherapy treatment was developed. The idea of aerosolization is to able direct delivery of a niosome formulation to the smaller airways of the lung. Niosome is a closed-bilayer vesicle in aqueous media that formed from the self-assembly of nonionic surfactant with cholesterol (Chol). NGC was prepared using a very simple heating method and was further optimized by D-optimal mixture design. The optimized NGC with 2.00 wt.% of surfactant (Tween 65 : Span 60 with ratio of 2:1), 1.01 wt.% of cholesterol and 63.06 wt.% of glycerol solution was obtained, where the other components were kept constant. The actual particle size showed good correlation with the predicted particle size with residual standard error (RSE) value less than 5%. The physicochemical characterization of optimum NGC formulation showed that the particle size, polydispersity index (PDI), and zeta potential were 166.45 nm, 0.16, and −15.28 mV, respectively. Zeta potential obtained indicates good stability against aggregation meanwhile if the zeta potential approaching zero value will lead to aggregation. The optimized NGC remained stable at 27°C with no phase separation for up to 90 days. Optimized NGC surface tension was 35.49 mN/m with an aerosol output of 96.22%, which indicates its suitability as aerosolized formulation. An in vitro drug release study using the dialysis bag diffusion technique showed controlled release for both drugs for up to 24 h penetration. The result showed that percentage of Gem release in pH 7.4 (64.71%) was 2-fold than Gem in pH 6.7 (30.38%). Meanwhile, for Cis, the percentage drug release in pH 7.4 was lower (53.55 %) than in pH 6.7 (99.58%) after 24h. This was due to the nature of drug and pH of the release medium affect the percentage of drug release. A cytotoxicity study against normal lung (MRC5) and lung cancer (A549) cell lines were performed by diluting and pipetting the formulation onto the cells. The results showed that the optimized NGC had reduced the cytotoxicity effects against both MRC5 and A549 cell lines when compared with the control (Gem + Cis alone) from very toxic (IC50 < 1.56 μg/mL) to weakly toxic (IC50 = 280.00 μg/mL) and moderately toxic (IC50 = 46.00 μg/mL), after 72 h of treatment. These results suggested that optimized NGC has the potential to be used for aerosolized chemotherapy treatment which will be promising less toxicity toward normal cell and able to inhibit cancer cell with low multidrug dosage.